Validity and Reliability of the Columbia Health Screen (CHS),Instrument of the Youth Mental Health and Suicide Screening program of Rosario University, Bogota, a Subsidiary of the Columbia University TeenScreen Program (2012)
Objetivos: evaluar la validez y confiabilidad de la versión hispana del instrumento de Tamizaje Juvenil (Encuesta de Salud Juvenil, ESJ) de la Universidad de Columbia aplicados en 2009 por el Programa de Salud Mental Juvenil de la Universidad del Rosario (UR) en el 8avo grado del Centro Educativo Integral de Colsubsidio (CEIC) en Bogotá, Colombia Metodología: Diseño observacional de evaluación de prueba diagnóstica tipo tamizaje en las dos etapas consecutivas del Programa de Tamizaje Juvenil aplicado en 183 alumnos. Evaluación de la reproducibilidad de las pruebas aplicadas a una sub muestra de 63 alumnos calculado con un muestreo aleatorizado por afijacion proporcional en un intervalo de 20 días. Resultados: el instrumento Encuesta de Salud Juvenil (ESJ) mostró una alta sensibilidad (100 %) y adecuada especificidad (89,09 %), un valor predictivo positivo del 85,88 % lo que le confiere adecuada validez. La confiabilidad y consistencia interna de la prueba son buenas, Alfa de Cronbach: 0,700, así como la concordancia de la ESJ inicial y la entrevista clínica de la segunda etapa del tamizaje (Kappa de 0.867, error estándar de 0.037 (p<0.001)). La reproducibilidad mostró un índice de Kappa de 0,645 en la sub muestra evaluada 20 días después. Conclusiones: la versión hispana del instrumento de Tamizaje Juvenil de la Universidad de Columbia tiene validez y confiabilidad adecuada para la detección de conducta suicida y signos de enfermedad mental en adolescentes. Ninguno Objectives: To assess the validity and reliability of the Hispanic version of the tools of the Columbia University Teen Screen applied in 2009 by the Youth Mental Health Program at the Rosario University (UR) in the 8thgrade at the Centro Educativo Integral de Colsubsidio (CEIC) in Bogotá, Colombia. Methodology: Observational design to assessment diagnosed type screening test in two consecutive steps of the Mental Health Screening program applied in 183 students. Evaluation of the reproducibility of the tests applied to a sub sample of 63 students estimated using a random sampling of proportional allocation in an interval of 20 days. Results: The tools of Hispanic version of the Columbia University Teen Screen showed a high sensitivity (100%) and adequate specificity (89.09%), positive predictive value 85,88% giving it adequate validity. The reliability and internal consistency of the test are good, Cronbach's alpha: 0.700, and the coherence of the initial ESJ and the clinical interview of the second stage of screening (kappa 0.867, standard error of 0,037 (p <0,001)). The reproducibility of the study showed a Kappa index of 0.645 in the sub sample assessed 20 days later. Conclusions: The Hispanic version of the tools of the Columbia University Teen Screen has adequate validity and reliability for detecting signs of suicidal behavior and mental illness in adolescents. Keywords: Screening Program, Validity, Reliability, Adolescents, Suicidal behavior.